Secondhand Smoke Exposure and Smoking Attitudes and Behaviors Among Adolescents in the Gaza Strip: Findings From the 2019 Global Youth Tobacco Survey - Beesan Maraqa; Mahmoud Abu Mayaleh; Seya Arafeh; Kenana Altell; Ahmad Khleif; Abdallah Najjar; Bayyena Abu-Radwan (Tobacco Use Insights)
Background Secondhand smoke (SHS) exposure remains a critical public health concern, especially for adolescents, who are more susceptible to its harmful effects and may initiate smoking as a result. SHS, comprising both mainstream and sidestream smoke, contains over 7000 chemicals, many of which are carcinogenic. Adolescents exposed to SHS are more likely to experiment with smoking due to environmental influences, peer pressure, and familial smoking behavior. Objective This study aims to examine the relationship between SHS exposure and smoking attitudes and behaviors among adolescents aged 13-15 in the Gaza Strip, where SHS exposure and tobacco use remain prevalent. Methods Data were obtained from the 2019 Global Youth Tobacco Survey (GYTS), a cross-sectional, school-based survey targeting students in Gaza. The study employed a two-stage cluster sampling design to ensure a representative sample. SHS exposure was assessed in multiple contexts, including home, public enclosed spaces, and outdoor areas. Smoking attitudes, initiation behaviors, and demographic variables were also analyzed using descriptive statistics, Chi-square tests, and multivariable logistic regression to identify predictors of smoking behaviors. Results Of the 1536 adolescents surveyed, 62.3% reported SHS exposure at home, and 53.9% reported exposure in enclosed public spaces. Adolescents exposed to SHS were significantly more likely to experiment with smoking, with curiosity (62.2%) and peer influence being key motivators. Additionally, SHS exposure in both indoor and outdoor environments was associated with a higher likelihood of shisha experimentation. Females reported higher SHS exposure rates than males across all environments ( P < .001). Conclusion SHS exposure significantly increases the risk of smoking initiation among adolescents in the Gaza Strip. These findings emphasize the need for targeted public health interventions, including stricter smoke-free legislation, parental education, and awareness campaigns aimed at reducing SHS exposure and preventing smoking uptake in youth.